2020
DOI: 10.1245/s10434-020-09161-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Primary Side and RAS/RAF Mutations in a Surgical Series of Colorectal Cancer with Peritoneal Metastases

Abstract: Background. Selecting patients with colorectal cancer peritoneal metastases (CRC-PMs) for surgery is still a concern. Biological features have the potential to improve prognostic stratification, but their significance in this clinical setting is still unclear. We assessed the prognostic impact of primary side and KRAS/NRAS/BRAF/PIK3CA mutations in patients treated with either cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) or CRS alone. Methods. We reviewed a prospective databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
3
20
1
Order By: Relevance
“… 62–64 In contrast, other studies cannot report on such significant prognostic differences between KRAS mutant and wild-type tumors. 65–68 With regard to BRAF mutations, comparable findings are reported, with several studies suggesting an impaired prognosis in colorectal PM patients with a BRAF mutation. 64 , 65 , 69 Two small studies did not find significant prognostic value of BRAF mutations, probably because of the low number of BRAF mutated tumors.…”
Section: Raf/ras Mutationssupporting
confidence: 71%
See 1 more Smart Citation
“… 62–64 In contrast, other studies cannot report on such significant prognostic differences between KRAS mutant and wild-type tumors. 65–68 With regard to BRAF mutations, comparable findings are reported, with several studies suggesting an impaired prognosis in colorectal PM patients with a BRAF mutation. 64 , 65 , 69 Two small studies did not find significant prognostic value of BRAF mutations, probably because of the low number of BRAF mutated tumors.…”
Section: Raf/ras Mutationssupporting
confidence: 71%
“… 65–68 With regard to BRAF mutations, comparable findings are reported, with several studies suggesting an impaired prognosis in colorectal PM patients with a BRAF mutation. 64 , 65 , 69 Two small studies did not find significant prognostic value of BRAF mutations, probably because of the low number of BRAF mutated tumors. 63 , 67 To assess the specific implications of RAS/RAF mutations in colorectal PM, the exact etiology of the possible prognostic impact of RAS/RAF mutations in colorectal cancer needs to be better understood.…”
Section: Raf/ras Mutationssupporting
confidence: 71%
“…Survival after CRS-HIPEC was first reported in a large study where Schneider et al found that both KRAS and BRAF mutations had a worse median cancer-specific survival: 18 months for mut BRAF , 38 months for mut KRAS compared to 52 months for double-wt patients [ 22 ]. In another study on 152 patients with CRS, results from next-generation sequencing technology were available for 68 cases: BRAF mutations (6.6%), but not mut KRAS (46.7%) were associated with worse survival [ 47 ]. Graf et al found that BRAF mutations among 111 patients with PM-CRC were an independent negative prognostic marker for survival, but not KRAS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that mutations in genomic driver genes impact on OS after CRS and HIPEC, but underlying studies were not randomized trials and mostly included a low number of patients. Furthermore, recent studies have revealed that BRAF mutations are associated with reduced OS, but no information is provided on the proportion of peritoneal and distant recurrent disease [ 40 , 41 ]. For the present time, evidence is too scarce to refuse these patients CRS and HIPEC in the event of detected mutations, because the true rate of peritoneal recurrent disease in KRAS- and BRAF-mutated patients undergoing CRS and HIPEC is not known.…”
Section: Discussionmentioning
confidence: 99%